Psychometric properties of the Pediatric Nurses’ Knowledge and Attitudes Survey Regarding Pain (PNKAS). An Italian multisite cross-sectional validation study - Bonfrate, Ismaela; Loia, Arianna; Ferri, Andrea; Demoro, Giuseppe; Cossalter, Luca; Murano, Liana; D'Alessandro, Antonella; Fermi, Lara; Milani, Margherita; Russello, Giuseppe; Cataldi, Giusy; Margosio, Viola; et al. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background and aim. Several studies have highlighted a lack of nursing knowledge regarding the assessment and management of pediatric pain. Because there is currently no specific tool for the assessment of pain knowledge in pediatric nursing professionals in Italy, the aim of the study was to translate into Italian, adapt, and validate the questionnaire “Pediatric Nurses’ Knowledge and Attitudes Survey Regarding Pain, in order to analyze its psychometric properties, providing a suitable tool for the assessment of pain.Study design. A multisite cross-sectional validation study was conducted and a convenience sample of italian nurses was enrolled.Results. A total of 233 nurses responded. Analyses demonstrated the “Pediatric Nurses’ Knowledge and Attitudes Survey Regarding Pain” factorial validity and internal consistency. The overall Cronbach’s alpha coefficient of the scale was 0.728. Pearson’s correlation coefficient was calculated between the test and retest phase, obtaining a value of r = 0.712 (p < .001). The intraclass correlation coefficient was 0.801 (95% confidence interval = 0.428-0.806). The Infit and Outfit statistical analysis fell within acceptable ranges from 0.85 to 2.50. The item difficulty ranged from −2.64 to 2.51. Out of total of 9,553 questions, 5,717 were answered correctly (correct answer rate 59.8%). No questionnaire had 80% or less of the correct answers.Conclusion. The scale designed in this study is valid and reliable for use in the Italian context and is applicable where one wants to evaluate nursing knowledge on the subject of pediatric pain.